Crepidiastrum denticulatum Extract Protects the Liver Against Chronic Alcohol-Induced Damage and Fat Accumulation in Rats - Yoo, Ji-Hye; Kang, Kyungsu; Yun, Ji Ho; Kim, Mi Ae; Nho, Chu Won (MARY ANN LIEBERT, INC, 2014)
Alcohol is a severe hepatotoxicant that causes liver abnormalities such as steatosis, cirrhosis, and hepatocarcinoma. Crepidiastrum denticulatum (CD) is a well-known, traditionally consumed vegetable in Korea, which was recently reported to have bioactive compounds with detoxification and antioxidant properties. In this study, we report the hepatoprotective effect of CD extract against chronic alcohol-induced liver damage in vivo. The rats that were given CD extract exhibited decreased alanine aminotransferase, aspartate aminotransferase, and c-glutamyl transpeptidase activities, which are liver damage markers that are typically elevated by alcohol consumption. The results were confirmed by histopathology with hematoxylin and eosin staining. Chronic alcohol consumption induced the formation of alcoholic fatty liver. However, treatment with CD extract dramatically decreased the hepatic lipid droplets. Treatment with CD extract also restored the antioxidative capacity and lipid peroxidation of the liver that had been changed by alcohol consumption. Furthermore, treatment with CD extract normalized the activities of the antioxidative enzymes superoxide dismutase, catalase, glutathione reductase, and glutathione peroxidase, which had been decreased by alcohol consumption. The results indicate that CD extract has protective effects against chronic alcohol hepatotoxicity in rats by increasing the liver's antioxidant capacity, and has potential as a dietary supplement intervention for patients with alcohol-induced liver damage.
Keywords: CHRONIC ETHANOL-CONSUMPTION; OXIDATIVE STRESS; SUPEROXIDE-DISMUTASE; HOVENIA-DULCIS; CELLS; CYCLODEXTRINS; REDUCTASE; CATALASE; ASSAYS; ACID